DESIGN OF EARTHQUAKE-RESISTANT REINFORCED CONCRETE STRUCTURE OF AN EIGHT-STOREY FLATS IN PONTIANAK CITY - Amin, Uray Maulaya Khoiriyah; Yusuf, Muhammad; Elvira, Elvira (Jurnal Teknik Sipil, 2023)
The mild to moderate earthquake zone includes the West Kalimantan region, especially Pontianak City. Along with the development of science, regulations governing building construction are continuously updated. SNI 1726-2019 results in that every building in the current mild earthquake zone must consider the earthquake force parameters so as not to cause a significant loss impact. Therefore, the design of an eight-story flats structure located in Pontianak will be carried out to obtain the dimensions of structural components resistant to earthquake loads based on SNI 1726-2019. This building design is a reinforced concrete structure with a moment-bearing frame system, and the structural analysis is modeled with a structural analysis program. The structural dimensions used are 100 mm thick floor plates, 350/700 mm and 400/800 mm for the primary beams, 250/500 mm for the secondary beam, and 800x800 mm columns. This building is included in KDS C, so the earthquake force-bearing structural system used is the Medium Moment Bearing Frame System (SRPMM). This structure has a type 2 horizontal deviation or inner corner deviation and a type 2 vertical deviation or weight (mass) deviation. Based on the structural analysis results, it is then adjusted to the structural parameters by the Indonesian National Standard (SNI). The results of the structural analysis are then continued with the calculation of reinforced concrete structures in accordance with the Indonesian National Standard (SNI) to ensure that the results meet the required safety criteria.